2013
DOI: 10.1890/es13-00012.1
|View full text |Cite
|
Sign up to set email alerts
|

Field colonies of leaf‐cutting ants select plant materials containing low abundances of endophytic fungi

Abstract: Abstract. Endophytic fungi live symbiotically in the tissues of plants. Although a large amount of evidence suggests a mutualistic role for vertically transmitted endophytic fungi in agronomic grasses, the role of horizontally transmitted endophytic fungi as mutualists has been challenged. Recent studies, however, have shown that horizontally transmitted endophytic fungi can act as mutualists to their plant hosts by providing defense against pathogens and defoliators. In particular, several experimental studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Interactions between insects and foliar endophytic fungi are less studied (Albrectsen and Witzell 2012), but there are indications that insects may actively avoid leaves with high abundance of endophytic fungi (Van Bael et al 2009; Coblentz and Van Bael 2013), although this is not always the case (Faeth and Hammon 1996). …”
Section: Discussionmentioning
confidence: 99%
“…Interactions between insects and foliar endophytic fungi are less studied (Albrectsen and Witzell 2012), but there are indications that insects may actively avoid leaves with high abundance of endophytic fungi (Van Bael et al 2009; Coblentz and Van Bael 2013), although this is not always the case (Faeth and Hammon 1996). …”
Section: Discussionmentioning
confidence: 99%
“…This result might be explained by the constant surveillance of ants because worker ants need to protect their gardens against alien fungi (Currie & Stuart 2001;Currie 2001;Van Bael et al 2009). Thus, independent from sampling area or period, using chemical and behavioural defences, ants try to reduce the loads of fungi that are incorporated in the garden matrix (Coblentz & Van Bael 2013) avoiding putative antagonism with the ant fungal cultivar (Silva et al 2006;Folgarait et al 2011). Another factor that may explain similarities in fungal diversity is the high abundance of the genera Escovopsis, Escovopsioides, and Trichoderma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the ants prefer leaves with low loads of endophytic fungi because the insects take more time cleaning the plant material with the higher abundances of fungi (Bittleston et al 2011). According to Coblentz & Van Bael (2013), preference for leaves with a low abundance of endophytic fungi is advantageous due to various factors: (i) showing preference allows the ants to avoid competition between the endophytic fungi and the mutualist fungus (either a direct effect or indirectly by production of secondary compounds) and (ii) the endophytes may have a toxic effect on the ants.…”
Section: Discussionmentioning
confidence: 99%
“…For example, bumblebee foragers are repelled by flowers contaminated with a protozoan flagellate parasite Crithidia bombi [27]. In Atta ant species, major foragers avoid retrieving leaves carrying a high microbial load or containing fungal endophytes, while small workers clean the retrieved leaf fragments of potential pathogens such as Metarhizium anisopliae spores [28][29][30]. These behaviours contribute to protecting the mutualistic fungal crop from competitive and pathogenic microbes.…”
Section: Introductionmentioning
confidence: 99%